Workshop Pembelajaran Geometri Berbasis Bukti melalui Pemanfaatan DGS Mathigon - As Elly; Yusuf Hartono; Nyimas Aisyah; Hapizah Hapizah (LP4MK STKIP PGRI Lubuklinggau, 2026)
This workshop aims to improve the competence of teachers and prospective teachers in designing and using DGS Mathigon technology-based learning media to teach geometric proofs and provide a deeper understanding of the importance of introducing geometric proofs in the classroom. Participants consisted of teachers and prospective mathematics teachers who were introduced to the basic concepts of proof and how Mathigon can be used to visualize geometric concepts and clarify the proof process. The workshop implementation method was carried out through conceptual sessions, practice, and evaluation of the results of the participants' work. The results of the analysis of the participants' assignments showed the participants' abilities in designing geometric proof problems and using technology-based teaching media, namely Mathigon. A self-evaluation questionnaire showed that 85% of participants felt the material presented was very useful and relevant, and 75% felt more prepared to integrate Mathigon in their teaching. Overall, this workshop successfully introduced technology that can enrich geometry teaching, making learning more interactive and interesting for students.